Local community participation in tourism development at Sedim, Kulim, Kedah - Fauzi, St Rabiatul Adawiyah (2016)
Community involvement and participation in leisure and tourism has become increasingly popular in Malaysia. The objectives of this study are to identify the role of local community and to identify the benefit gain by the local community through the participation in tourism development at Sedim, Kulim, Kedah. This study presents the result of a quantitative method through survey which 200 respondents from the local community have been given the questionnaire. Method used was random sampling. The data collected was analyzed using SPSS (Statistical Package for the Social Sciences). Through the analysis done it has was proven that the local community wants to give opinion in the decision making process and also should be consulted but the final decision on the tourism development should be made by formal bodies. Besides, the local community also admits that the benefit gain by participating in tourism development has improved general quality of life and it provides employment opportunities for local people. In addition, local community sees the tourism development in a positive way. This finding can help the authority in making decision and make the local community participate in every aspect of tourism development at Sedim.